Effects of Citric Acid and Lactobacillus plantarum on Silage Quality and Bacterial Diversity of King Grass Silage - Zi, Xuejuan; Li, Mao; Chen, Yeyuan; Lv, Renlong; Zhou, Hanlin; Tang, Jun (Frontiers in Microbiology, 2021)
To better understand the mechanism underlying the citric acid (CA)-regulated silage fermentation, we investigated the bacterial community and fermentation quality of king grass (KG) ensiled without (CK) or with Lactobacillus plantarum (L), CA and the combination of L and CA (CAL). The bacterial community was characterized by using the 16Sr DNA sequencing technology. The L and CA treatments altered the silage bacterial community of KG, showing reduced bacterial diversity, while the abundance of desirable genus Lactobacillus was increased, and the abundances of undesirable genus Dysgonomonas and Pseudomonas were decreased. The additives also significantly raised the lactic acid content, dropped the pH, and reduced the contents of acetic acid, propionic acid, and ammonia-N in ensiled KG (P <0.01). Besides, the combination treatment was more effective on silage fermentation with the highest pH and lactic acid content, while the contents of acetic acid, propionic acid, and ammonia-N were the lowest (P <0.01). Moreover, CAL treatment exerted a notable influence on the bacterial community, with the lowest OTU number and highest abundance of Lactobacillus. Furthermore, the bacterial community was significantly correlated with fermentation characteristics. These results proved that L and CA enhanced the KG silage quality, and the combination had a beneficial synergistic effect.